STUDI CITRA RUMAH SAKIT DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA RUMAH SAKIT AWAL BROS TANGERANG - Agung Sulistyo; Aris Gumilar (JMB : Jurnal Manajemen dan Bisnis, 2019)
This study aims to determine the effect of hospital image and service quality to customer loyalty through customer satisfaction at Awal Bros Tangerang Hospital. The research method used in this research is descriptive method, and by testing the hypothesis. The result of the study found that: 1) There is a positive direct effect of Hospital Image on Customer Satisfaction of Awal Bros Tangerang. 2) There is a positive direct influence Quality of service to Customer Satisfaction Awal Bros Tangerang Hospital. 3) There is a positive direct influence Customer Satisfaction on Customer Loyalty Awal Bros Tangerang Hospital. 4) There is a positive direct impact Hospital image of Customer Loyalty Awal Bros Tangerang Hospital.5) There is a positive direct effect quality of service to Customer loyalty Awal Bros Tangerang Hospital. 6) There is no positive indirect influence of Hospital Image on Customer loyalty through Customer Satisfaction of Awal Bros Tangerang Hospital. 7) There is an indirect effect of service quality on Customer Loyalty through Customer Satisfaction  Awal Bros Tangerang Hospital.